Numerical investigation of the flow field in confined impinging jets of power law fluids - Adélio Cavadas (2007)
A numerical investigation was carried out to characterize the isothermal flow in a confined impinging jet emanating from a rectangular duct of aspect-ratio equal to 13. After impinging a flat plate the flow separated in two streams that were confined by two slopping plane walls, each making an angle of 12° relative to the plate. The fluids were Newtonian and purely viscous non-Newtonian, the latter described by a power law model. The numerical simulation was carried out with a finite-volume based code using non-orthogonal collocated grids and second order accurate differencing schemes to discretize all terms of the transport equations. The flow characteristics were studied as a function of shear-thinning intensity for Reynolds numbers between 10 and 800. Specifically, we investigate in detail the pressure loss in the cell and the size of the recirculation zone attached to the sloping surfaces of the cell after validation of the numerical simulations against experimental Newtonian and non-Newtonian data. Three dimensional effects due to the finite span of the rectangular duct and cell are also evaluated.